Mesoporous hollow lithium silicate microspheres and a preparation method thereof
Patent Information
- Application Number
- CN202611108716.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-20
AI Technical Summary
[0006]有鉴于此,本发明的目的在于提出一种介孔空心硅酸锂微球及其制备方法,以解决现有技术中介孔空心球硅酸锂制备工艺复杂、结构调控精度低、循环稳定性差、功能单一的问题
(1)本发明基于酚醛聚合与硅源水解的速率差异,通过时间差调控即可实现空腔尺寸连续可调,无需复杂硬模板;通过多阶时序投料,可简单可控地制备复杂分级结构,解决了现有技术中硅酸锂空心结构制备繁琐、调控精度低的难题。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic functional nanomaterial preparation technology, and in particular to a mesoporous hollow lithium silicate microsphere and its preparation method. Background Technology
[0002] Lithium silicate (including phases such as Li₂SiO₃ and Li₄SiO₄) is a class of lithium-based inorganic functional materials that combine high theoretical capacity, environmental friendliness, and abundant resources, and has important application value in electrochemical energy storage, high-temperature gas adsorption, and catalysis. However, traditional lithium silicate is mostly solid random particles, which have inherent defects such as long ion diffusion paths, low exposure of active sites, significant volume effects, and easy structural collapse during cycling, which seriously restrict its performance and large-scale application.
[0003] Hollow mesoporous structures possess both the volumetric buffer space of the internal cavity and the rapid mass transfer channel of the mesoporous shell, representing a core structural design direction for solving the aforementioned problems. Currently, the preparation of silicon-based hollow mesoporous materials has formed various technical routes, including template methods, etching methods, and self-templating methods. However, the direct preparation of mesoporous hollow lithium silicate still faces many bottlenecks: Low structural control precision: Existing hard template method is complex, template removal can easily cause structural damage, making it difficult to achieve multi-dimensional precise control of cavity size, shell thickness and mesopore diameter; Poor structural stability: Pure lithium silicate has insufficient mechanical strength, and the hollow structure is prone to collapse during lithiation reaction and cycling, and the mesoporous order is easily destroyed; Limited functionality and poor conductivity: Pure-phase lithium silicate has low electronic conductivity, resulting in poor rate performance when used in electrochemical scenarios, and it is difficult to simultaneously meet the needs of multiple scenarios such as adsorption, catalysis, and controlled release.
[0004] In existing technologies, the preparation techniques for hollow mesoporous silica are relatively mature: the soft / hard dual-template method can prepare highly ordered mesoporous hollow silica spheres, the polymerization-hydrolysis timing control method can achieve continuous control of cavity size through a simple reaction time difference, and core-shell mesoporous silica microspheres can combine size exclusion and adsorption separation functions. However, the technical route for converting silica-based materials into high-performance mesoporous hollow lithium silicate is still imperfect, and it is impossible to simultaneously achieve structural controllability, structural stability, and functional diversity.
[0005] Therefore, based on the relevant technologies mentioned above, there is an urgent need to develop a mesoporous hollow lithium silicate microsphere and its preparation method. Summary of the Invention
[0006] In view of this, the purpose of this invention is to propose a mesoporous hollow lithium silicate microsphere and its preparation method, so as to solve the problems of complex preparation process, low structural control precision, poor cycle stability and single function of existing mesoporous hollow lithium silicate microspheres.
[0007] To achieve the above objectives, the mesoporous hollow lithium silicate microspheres provided by this invention possess a core-shell hierarchical mesoporous structure. The microspheres are monodisperse spheres with an internally sized, closed cavity. The shell layer is composed of a mesoporous lithium silicate phase, and a continuous amorphous carbon framework is in situ composited within the shell layer. The amorphous carbon phase is uniformly distributed within the lithium silicate shell layer, serving both as a rigid support network to enhance structural stability and as a continuous conductive pathway to improve electron transport efficiency.
[0008] A mesoporous hollow lithium silicate microsphere has a core-shell hierarchical hollow mesoporous structure, with an internally sized closed cavity and a shell layer consisting of a mesoporous lithium silicate phase, in situ composited with an amorphous carbon framework. The microspheres have a particle size of 200 nm-2 μm, a cavity diameter of 50 nm-1 μm, a shell thickness of 50-500 nm, a mesopore size of 2-20 nm, and a BET specific surface area of 300-1300 m². 2 / g; The lithium silicate is one or a mixture of two of Li2SiO3 and Li4SiO4; the mass of the amorphous carbon skeleton accounts for 1%-30% of the total mass of the microspheres.
[0009] Preferably, the amorphous carbon skeleton is a heteroatom-doped modified carbon skeleton, and the heteroatoms are one or more of nitrogen, phosphorus, and sulfur, with the heteroatom doping amount accounting for 1%-15% of the total mass of the carbon skeleton.
[0010] Preferably, the shell layer contains an in-situ composite nano-second phase to form a lithium silicate heterojunction. The nano-second phase is one or more of Li2TiO3, ZnO, Co3O4, and SnO2, and its mass accounts for 2%-20% of the total mass of the microspheres.
[0011] Preferably, the microspheres have a double-shell or triple-shell hierarchical hollow structure, each shell being a mesoporous lithium silicate composite carbon skeleton structure, with buffer cavities between adjacent shells.
[0012] A method for preparing mesoporous hollow lithium silicate microspheres includes the following steps: Step S1. Precursor Preparation with Time-Controlled Processing: In an alkaline alcohol-water mixture system with pH 8-11, phenolic and aldehyde monomers are first added for polymerization, with the polymerization time controlled at 0.5-3 hours. The growth degree of resin oligomers is controlled by adjusting the polymerization time. Then, a silicon source is added for hydrolysis and condensation polymerization. After the reaction, the mixture is separated, washed, and dried to obtain SiO2@phenolic resin@SiO2 three-layer core-shell structure precursor microspheres. Utilizing the controllable hydrolysis rate of the silicon source, a silica layer is simultaneously formed in the resin core and solution, resulting in SiO2@phenolic resin@SiO2 three-layer core-shell structure precursor microspheres. By precisely controlling the time difference between the polymerization and hydrolysis reactions, the core layer size and composition of the precursor can be continuously controlled, ultimately achieving precise control of the product cavity size.
[0013] Step S2. Carbonization and curing treatment: The precursor microspheres are carbonized at high temperature in an inert atmosphere, and the phenolic resin is transformed into an amorphous carbon skeleton to obtain SiO2@SiO2 / C@SiO2 composite microspheres. During high-temperature carbonization, the phenolic resin is transformed into amorphous carbon to form a continuous carbon skeleton, which not only improves the conductivity of the material, but also provides structural support for the subsequent etching and lithiation process, preventing the collapse of the hollow structure.
[0014] Step S3. Selective etching to create pores: The carbonized composite microspheres are placed in a dilute hydrofluoric acid solution for etching. By adjusting the concentration of hydrofluoric acid and the etching time, some of the silicon dioxide is selectively removed, and internal hollow cavities and shell mesoporous channels are formed simultaneously to obtain mesoporous hollow SiO2 / C microspheres. Step S4. Solid-phase lithiation reaction: Mesoporous hollow SiO2 / C microspheres are uniformly mixed with a lithium source and subjected to a high-temperature solid-phase reaction. Silicon dioxide is converted into lithium silicate while the carbon skeleton remains stable, ultimately yielding mesoporous hollow lithium silicate microspheres.
[0015] Preferably, in step S1, during the polymerization reaction of phenolic monomers and aldehyde monomers, a heteroatom dopant source is simultaneously added. The heteroatom dopant source is one or more of melamine, thiourea, phytic acid, and urea, and the added mass is 5%-50% of the mass of the phenolic monomers. Preferably, in step S4, a second metal source is added simultaneously when mixing with the lithium source. The second metal source is one or more of titanium, zinc, cobalt, and tin sources, and the amount added is based on a molar ratio of metal element to silicon element of 0.02-0.2:1. During the high-temperature solid-phase reaction, a nano-second phase is generated in situ to form a lithium silicate-based heterojunction.
[0016] Preferably, the preparation process of the precursor microspheres in step S1 includes the following steps: First, a first portion of silicon source is added and hydrolyzed to form the first SiO2 core. Then, phenolic monomers are added and polymerized to form the first resin layer. Next, a second portion of silicon source is added and hydrolyzed to form the first SiO2 shell. Then, phenolic monomers are added again and polymerized to form the second resin layer. Finally, a third portion of silicon source is added and hydrolyzed to form the second SiO2 shell. After carbonization, etching, and lithiation, double-shell mesoporous hollow lithium silicate microspheres are obtained. The time difference between polymerization and hydrolysis is controlled to be 2.5-3.5 h to form a SiO2@resin core@SiO2 shell structure. The internal SiO2 / C composite core is retained by carbonization and etching, and then lithium silicate microspheres are obtained by lithiation.
[0017] Preferably, the phenolic monomer in step S1 is one or more of resorcinol and phenol; the aldehyde monomer is one or more of formaldehyde and paraformaldehyde; and the silicon source is at least one of propoxysilane and tetraethyl orthosilicate. The hydrolysis-condensation reaction time in step S1 is 12-36 hours, and the reaction temperature is room temperature; In step S2, the carbonization temperature is 500-800℃, the holding time is 1-4h, and the heating rate is 1-10℃ / min.
[0018] Preferably, in step S3, the mass concentration of the dilute hydrofluoric acid solution is 2%-10%, and the etching time is 0.5-2 hours. The lithium source mentioned in step S4 is one or more of lithium hydroxide, lithium nitrate, lithium carbonate, and lithium acetate; the silicon-lithium molar ratio is 1:(1-4), the lithiation reaction temperature is 500-800℃, and the holding time is 2-6h; The microspheres are used in lithium-ion battery anode materials, carbon dioxide adsorbents, catalyst supports, and controlled release supports for active substances.
[0019] This invention can break through the performance limits of traditional carbon coating through functional modification of the carbon skeleton: introducing heteroatoms such as nitrogen, phosphorus, and sulfur in situ during the phenolic polymerization stage, introducing a large number of defects and active sites into the carbon skeleton, and improving electronic conductivity and interfacial adsorption capacity at the same time; it can also be combined with highly conductive carbon phases such as carbon nanotubes and graphene quantum dots to construct a multi-level conductive network of "amorphous carbon mechanical support and rapid electron transport of highly conductive phase", further reducing electron transport resistance.
[0020] Furthermore, the present invention can achieve functional leap through heterostructure construction: a second metal source is introduced in the lithiation stage to generate a nano-second phase in situ to construct a lithium silicate-based heterostructure, and the interfacial charge transfer effect is used to accelerate ion transport and improve electrochemical reaction kinetics; or a thin layer of metal-organic framework such as ZIF-8 can be coated on the surface of the microspheres to endow the material with pH-responsive release and precise sieving functions, which are suitable for pesticide controlled release, precise adsorption and other scenarios.
[0021] Furthermore, this invention can achieve structural hierarchical upgrades through multi-stage temporal regulation, preparing double-shell, triple-shell hierarchical hollow structures or yolk-shell structures. Multi-level cavities can provide progressive volume buffering and more active sites, significantly improving the long-term structural stability of the material.
[0022] The beneficial effects of this invention are: (1) Based on the rate difference between phenolic polymerization and silicon source hydrolysis, the cavity size can be continuously adjusted by time difference control, without the need for complex hard templates; through multi-stage time sequence feeding, complex hierarchical structures can be prepared simply and controllably, solving the problems of cumbersome preparation and low control precision of lithium silicate hollow structure in the prior art.
[0023] (2) This invention breaks through the technical prejudice that “carbon coating only improves conductivity”. By in-situ heteroatom doping, while ensuring the mechanical support and conductivity of the carbon skeleton, a large number of defective active sites are introduced, making the lithium storage capacity and CO2 adsorption capacity of the material significantly higher than the theoretical expected value of simple carbon coating. The multi-level conductive network can further improve the rate performance, realizing the synergistic enhancement of the carbon skeleton and the lithium silicate matrix.
[0024] (3) The in-situ heterojunction provided by the present invention utilizes the interfacial electric field effect to accelerate ion transport, solving the inherent shortcoming of low ion conductivity of pure lithium silicate; MOF coating endows the material with pH-responsive release characteristics, making it suitable for pesticide controlled release, precise adsorption and other scenarios. It is not a simple functional superposition, but a performance leap achieved through interfacial synergy.
[0025] (4) The microspheres provided by the present invention can provide progressive volume buffering, effectively relieving volume stress during cycling. The capacity retention rate can be increased to more than 88% after 600 cycles under a high current of 10A / g. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0027] Example 1: A method for preparing basic mesoporous hollow lithium silicate microspheres, comprising the following steps: Step S1. Preparation of time-controlled precursor: Add 70 mL of anhydrous ethanol, 1 mL of deionized water, and 3 mL of 28% ammonia water to a beaker, and stir until a pH≈9 alkaline alcohol-water system is formed. Add 0.4 g of resorcinol and stir for 5 min until completely dissolved; add 0.56 mL of 37% formaldehyde solution to start the phenolic polymerization reaction and control the polymerization time to 0.5 h. Then 1.73 mL of tetraethyl orthosilicate (TEOS) was added as a silicon source, and the reaction was continued with stirring for 12 h. After the reaction was completed, the product was collected by centrifugation, washed three times each with deionized water and anhydrous ethanol, and dried under vacuum at 60°C overnight to obtain SiO2@phenolic resin@SiO2 three-layer core-shell structure precursor microspheres.
[0028] Step S2. Carbonization and curing treatment: The precursor microspheres are placed in a tube furnace and heated to 500℃ at a heating rate of 1℃ / min under an inert argon atmosphere. The temperature is maintained for 1h for carbonization, and then naturally cooled to room temperature to obtain SiO2@SiO2 / C@SiO2 composite microspheres.
[0029] Step S3. Selective etching to create pores: Disperse the composite microspheres in a 2% (w / w) dilute hydrofluoric acid solution and etch at room temperature for 0.5 h; The product was collected by centrifugation, washed until the filtrate was neutral, and dried under vacuum at 60°C to obtain mesoporous hollow SiO2 / C microspheres.
[0030] Step S4. Solid-phase lithiation reaction: Mesoporous hollow SiO2 / C microspheres and lithium hydroxide are uniformly ground and mixed at a silicon-lithium molar ratio of 1:1. The mixture is placed in an air atmosphere in a muffle furnace and heated to 500℃ at a rate of 2℃ / min. The mixture is then held at this temperature for 2 hours to carry out a solid-phase lithiation reaction. After natural cooling, mesoporous hollow lithium silicate microspheres are obtained, with Li2SiO3 as the main crystalline phase.
[0031] In this embodiment, the amorphous carbon phase content of the microspheres is approximately 1.2%.
[0032] Example 2: A method for preparing nitrogen-doped mesoporous hollow lithium silicate microspheres, comprising the following steps: Step S1. Preparation of time-controlled precursor: Add 70 mL of anhydrous ethanol, 1 mL of deionized water, and 3 mL of 28% ammonia water to a beaker, and stir until homogeneous to form an alkaline alcohol-water system; Add 0.4 g resorcinol and 0.11 g melamine as a nitrogen dopant source, and stir for 5 min until completely dissolved; add 0.56 mL of 37% formaldehyde solution to start the phenolic polymerization reaction, and control the polymerization time to 1.5 h. Then 1.73 mL of n-propoxysilane (TPOS) was added as a silicon source, and the reaction was continued with stirring for 24 h. After the reaction was completed, the microspheres were centrifuged, washed, and dried to obtain in-situ nitrogen-doped SiO2@phenolic resin@SiO2 precursor microspheres.
[0033] Step S2. Carbonization and curing treatment: The precursor microspheres are placed in an argon atmosphere in a tube furnace and heated to 650°C at a heating rate of 5°C / min. The temperature is maintained for 2.5 hours for carbonization, and the composite microspheres are obtained by natural cooling.
[0034] Step S3. Selective etching to create pores: Disperse the composite microspheres in a 6% (w / w) dilute hydrofluoric acid solution and etch at room temperature for 1.25 h; After washing and drying, nitrogen-doped mesoporous hollow SiO2 / C microspheres were obtained.
[0035] Step S4. Solid-phase lithiation reaction: Mesoporous microspheres and lithium carbonate are uniformly mixed at a silicon-lithium molar ratio of 1:2.5, placed in a muffle furnace, heated to 650℃ at 5℃ / min, and held for 4h to carry out the lithiation reaction. After natural cooling, nitrogen-doped mesoporous hollow lithium silicate microspheres are obtained, with Li2SiO3 as the main crystalline phase.
[0036] In this embodiment, the amorphous carbon phase accounts for approximately 15.2% of the mass of the microspheres, and the nitrogen doping content in the carbon framework is approximately 8.1%.
[0037] Example 3: A method for preparing Li2TiO3 heterojunction mesoporous hollow lithium silicate microspheres, comprising the following steps: Step S1. Preparation of time-controlled precursor: Add 70 mL of anhydrous ethanol, 1 mL of deionized water, and 3 mL of 28% ammonia water to a beaker, and stir until homogeneous to form an alkaline alcohol-water system; Add 0.8g of resorcinol and stir for 5 minutes until completely dissolved; Add 1.12 mL of 37% formaldehyde solution to start the phenolic polymerization reaction and control the polymerization time to 3 h; Then 3.46 mL of n-propoxysilane (TPOS) was added as a silicon source, and the reaction was stirred for another 36 h. After the reaction was completed, the mixture was centrifuged, washed, and dried to obtain SiO2@phenolic resin@SiO2 precursor microspheres with high resin content.
[0038] Step S2. Carbonization and curing treatment: The precursor microspheres are placed in an argon atmosphere in a tube furnace and heated to 800℃ at a heating rate of 10℃ / min. The temperature is maintained for 4 hours for carbonization, and the composite microspheres are obtained by natural cooling.
[0039] Step S3. Selective etching to create pores: Disperse the composite microspheres in a 10% (w / w) dilute hydrofluoric acid solution and etch at room temperature for 2 hours; After washing and drying, high-carbon-content mesoporous hollow SiO2 / C microspheres were obtained.
[0040] Step S4. Solid-phase lithiation reaction: Mesoporous microspheres and lithium acetate are uniformly mixed at a silicon-lithium molar ratio of 1:4, and tetrabutyl titanate is added at a titanium-to-silicon molar ratio of 0.2:1. The mixture is then thoroughly ground and mixed evenly. The solid-state reaction was carried out in a muffle furnace by heating to 800℃ at 10℃ / min and holding for 6h to generate Li2TiO3 nano-second phase in situ, resulting in Li2TiO3 heterojunction mesoporous hollow lithium silicate microspheres with Li2SiO3 and Li2TiO3 composite phase as the main crystalline phase.
[0041] In this embodiment, the amorphous carbon phase of the microspheres accounts for approximately 29.3% of the mass, and the nano-second phase accounts for approximately 19.7% of the mass.
[0042] Comparative Example 1: This comparative example uses solid mesoporous lithium silicate (without hollow structure or carbon composite) as a control: The traditional sol-gel method was used to prepare solid mesoporous SiO2 microspheres by hydrolyzing tetraethyl orthosilicate. These microspheres were then mixed with lithium hydroxide at a silicon-to-lithium ratio of 1:2.2 and lithiated at 650°C for 4 hours to obtain solid mesoporous lithium silicate without hollow cavities or carbon phase composites.
[0043] Comparative Example 2: This comparative example uses surface carbon-coated hollow lithium silicate (non-in-situ carbon coating, without embedded carbon framework) as a control: First, pure hollow SiO2 microspheres (without phenolic carbon framework) were prepared by etching, and then lithiated at 650°C to obtain pure hollow lithium silicate. Subsequently, these microspheres were added to a glucose aqueous solution and hydrothermally heated at 180°C for 6 hours to coat the surface with carbon. After washing and drying, carbon-coated hollow lithium silicate was obtained. The carbon was only distributed on the outer surface of the microspheres, with no continuous carbon framework inside the shell. The total carbon mass percentage was approximately 7%, comparable to the carbon content in Example 1.
[0044] Comparative Example 3: This comparative example uses pure hollow lithium silicate (without carbon framework) as a control: the preparation process is the same as in Example 1, but resorcinol and formaldehyde are not added in step S1, hollow SiO2 microspheres are directly prepared, and pure hollow lithium silicate is obtained by lithiation, without carbon phase composite.
[0045] Comparative Example 4: This comparative example uses a physical mixture of nitrogen-doped carbon and hollow lithium silicate as a control: the mesoporous hollow lithium silicate prepared in Example 1 was physically ground and mixed with commercial nitrogen-doped carbon black at a mass ratio of 92:8, so that the total carbon content and nitrogen doping amount were basically the same as those in Example 2; the carbon phase and lithium silicate were simply physically mixed, without in-situ recombination and doping synergistic effect.
[0046] Comparative Example 5: This comparative example uses a physical mixture of Li2TiO3 and hollow lithium silicate as a control: the mesoporous hollow lithium silicate prepared in Example 1 was physically ground and mixed with commercial Li2TiO3 nanoparticles at a mass ratio of 80:20, so that the total content of the second phase was basically the same as that in Example 3; the two phases were a simple physical mixture with no heterojunction interface and charge transfer effect.
[0047] Comparative Example 6: This comparative example uses traditional hard-template mesoporous hollow lithium silicate as a control: monodisperse polystyrene microspheres (300 nm) are used as hard templates, coated with a mesoporous silica layer, and calcined at 550 °C to remove the polystyrene template, resulting in hollow mesoporous SiO2 microspheres; after mixing with lithium hydroxide, they are lithiated at 650 °C to obtain hard-template mesoporous hollow lithium silicate, without carbon phase composite.
[0048] Performance testing: The system performance of the samples prepared in Examples 1-3 and Comparative Examples 1-6 was tested using the following methods: Microstructure characterization: The morphology of microspheres was observed using a transmission electron microscope (TEM, JEM-2100F, 200kV). The average particle size, average cavity diameter, and average shell thickness were calculated from 100 randomly selected particles. The nitrogen adsorption-desorption isotherm was tested using a fully automated specific surface area and porosity analyzer (TriStar II 3020). The BET specific surface area and BJH average mesopore diameter were calculated. Before the test, the samples were degassed in vacuum at 120℃ for 10 h. Electrochemical lithium storage performance test: The active material, acetylene black conductive agent, and PVDF binder were mixed in a mass ratio of 7:2:1, and a uniform slurry was prepared using NMP as a solvent. This slurry was coated onto a copper foil current collector, vacuum dried at 110℃ for 12 hours, and then cut into Φ16mm electrode sheets. The active material loading was controlled at 0.6-0.8 mg / cm³. 2 CR2032 coin cells were assembled in an argon-atmospheric glove box (O2 / H2O < 0.1 ppm), with a lithium metal sheet as the counter electrode, Celgard 2325 as the separator, and 1 mol / L LiPF6 (EC / DMC = 1:1, v / v) as the electrolyte. Tests were conducted within a voltage window of 0.01–3.0 V: the reversible discharge specific capacity at current densities of 0.1 A / g and 5 A / g was recorded; after 600 cycles at a high current density of 10 A / g, the capacity retention rate was calculated as (600th discharge capacity / 2nd discharge capacity × 100%). CO2 adsorption performance test: The CO2 equilibrium adsorption capacity of the sample was tested using a high-precision gas adsorption instrument at 25℃ and 1 bar. Before the test, the sample was degassed in vacuum at 150℃ for 12 hours. Long-cycle structural stability test: The battery after 600 cycles at 10A / g was disassembled, the electrode plates were removed and the residual electrolyte was cleaned with dimethyl carbonate, and after vacuum drying, the microsphere structure morphology was observed by scanning electron microscopy (SEM). The proportion of structurally intact microspheres in 100 microspheres was counted and the structure retention rate was calculated. The structural parameters and performance test results of all samples are summarized in Tables 1-3 below.
[0049] Table 1. Comparison of structural parameters and performance of Examples 1-3 Table 2 Comparison of structural parameters and performance of Comparative Examples 1-3 Table 3. Comparison of structural parameters and performance of Comparative Examples 4-6 Data Analysis: As can be seen from Tables 1-3, comparing Example 1 with Comparative Examples 1, 2, and 3 shows that: Comparative Example 1 is a solid carbon-free lithium silicate with a specific capacity of only 785 mAh / g at 0.1 A / g and a capacity retention rate of only 42.1% after 600 cycles at 10 A / g, exhibiting the worst performance. This confirms the inherent defects of solid structures, such as long ion diffusion paths and large volume effects.
[0050] Comparative Example 3 is a pure hollow carbon-free lithium silicate, which has improved specific capacity and cycle performance compared to Comparative Example 1, but its rate performance and structural stability are still poor. This indicates that the single hollow structure can only partially alleviate the volume effect and cannot solve the problem of poor conductivity.
[0051] Comparative Example 2 is a hollow lithium silicate with surface carbon coating, which has better performance than the pure hollow structure, but is still significantly lower than the in-situ carbon skeleton scheme of Example 1.
[0052] The specific capacity of Example 1 was increased by 9.5% compared with Comparative Example 2, the cycle capacity retention rate was increased by 11.2 percentage points, and the structure retention rate was increased by 13.4 percentage points.
[0053] The above differences demonstrate that the in-situ embedded continuous carbon framework not only improves conductivity but also forms a rigid support network within the shell, working in conjunction with the hollow structure to resist volumetric stress. Its structural stability is far superior to that of surface carbon coating. The synergistic effect of the two structures makes the material's overall performance far exceed the simple sum of "hollow structure and surface carbon coating."
[0054] Comparing Example 2 and Comparative Example 4, their carbon and nitrogen contents are basically the same. The difference lies in that Example 2 uses in-situ nitrogen-doped carbon framework, while Comparative Example 4 uses physically mixed nitrogen-doped carbon. The specific capacity of Example 2 at 0.1 A / g is increased by 15.4%, the specific capacity at 5 A / g is increased by 28.2%, the CO2 adsorption capacity is increased by 24.6%, and the cycle retention rate is increased by 12.3 percentage points compared to Comparative Example 4. The core reason for the difference is that in-situ doping allows nitrogen atoms to be uniformly embedded in the carbon framework lattice, introducing a large number of defective active sites. This not only improves the electronic conductivity of the carbon framework but also provides additional lithium storage and adsorption active sites at the carbon-lithium silicate interface, achieving a dual effect of "conductivity enhancement and active site replenishment." In contrast, physically mixed nitrogen-doped carbon can only conduct electricity between particles and cannot form an interfacial synergy with the lithium silicate matrix.
[0055] Existing technologies generally believe that carbon coating only plays a conductive role. This invention, through in-situ heteroatom doping, enables the material's lithium storage capacity and gas adsorption capacity to exceed the theoretical expected values of simple carbon coating, verifying the synergistic effect of carbon framework functionalization and lithium silicate matrix, and breaking through the technical understanding in this field.
[0056] Comparing Example 3 and Comparative Example 5, the second phase content of both is basically the same. The difference lies in that Example 3 uses an in-situ heterojunction, while Comparative Example 5 uses a physically mixed second phase. The 5A / g specific capacity of Example 3 is 51.3% higher than that of Comparative Example 5, the cycle capacity retention is improved by 18.1 percentage points, and the rate performance improvement is particularly significant. The difference stems from the fact that the in-situ heterojunction forms a built-in electric field at the interface between the two phases, which can accelerate interfacial charge transfer and lithium-ion transport, significantly improving reaction kinetics; while the physically mixed two-phase interface has poor contact and cannot produce an interfacial charge transfer effect, only achieving a simple superposition of performance. This result proves that the in-situ heterostructure is not a simple superposition of the functions of the two phases, but rather achieves a performance leap in electrochemical kinetics through interfacial synergy, which is a non-obvious functional improvement.
[0057] Comparing Example 1 with Comparative Example 6, both are single-shell hollow structures, but their preparation processes differ: Example 1 exhibits a higher BET specific surface area and more uniform mesopore distribution, demonstrating superior electrochemical performance and structural stability compared to products prepared using the hard template method. Furthermore, the preparation process eliminates the need for template calcination removal, resulting in a simpler process and more precise structural control. Moreover, this invention allows for the further preparation of complex structures such as multi-shell structures and yolk-shell structures through multi-stage temporal control, whereas the hard template method struggles to achieve controllable preparation of multi-shell structures, fully demonstrating the versatility and technological advantages of this invention.
[0058] In summary, this invention achieves multiple synergies in structure, composition, and interface through a systematic design of "time-controlled precise nucleation, in-situ carbon framework composite, and functional modification and upgrading." The improvement in various performance aspects exceeds the conventional expectations of those skilled in the art, demonstrating significant inventiveness and practical value.
[0059] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.
[0060] This invention is intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention should be included within the scope of protection of this invention.
Claims
1. A mesoporous hollow lithium silicate microsphere, characterized in that, The microspheres possess a core-shell hierarchical hollow mesoporous structure, with an internally sized, closed cavity. The shell layer is a mesoporous lithium silicate phase, and an amorphous carbon framework is in situ composited within the shell layer. The microspheres have a particle size of 200 nm-2 μm, a cavity diameter of 50 nm-1 μm, a shell thickness of 50-500 nm, a mesopore size of 2-20 nm, and a BET specific surface area of 300-1300 m². 2 / g; The lithium silicate is one or a mixture of two of Li2SiO3 and Li4SiO4; the mass of the amorphous carbon skeleton accounts for 1%-30% of the total mass of the microspheres.
2. The mesoporous hollow lithium silicate microspheres according to claim 1, characterized in that, The amorphous carbon skeleton is a heteroatom-doped modified carbon skeleton, and the heteroatoms are one or more of nitrogen, phosphorus, and sulfur, with the heteroatom doping amount accounting for 1%-15% of the total mass of the carbon skeleton.
3. The mesoporous hollow lithium silicate microspheres according to claim 1, characterized in that, The shell layer contains an in-situ composite of a nano-second phase, forming a lithium silicate heterojunction. The nano-second phase is one or more of Li2TiO3, ZnO, Co3O4, and SnO2, and its mass accounts for 2%-20% of the total mass of the microspheres.
4. The mesoporous hollow lithium silicate microspheres according to claim 1, characterized in that, The microspheres have a double-shell or triple-shell hierarchical hollow structure, with each shell being a mesoporous lithium silicate composite carbon skeleton structure and a buffer cavity between adjacent shells.
5. The method for preparing mesoporous hollow lithium silicate microspheres according to claim 1, characterized in that, Includes the following steps: Step S1. In an alkaline alcohol-water mixture system with pH 8-11, phenolic monomers and aldehyde monomers are first added to carry out a polymerization reaction, and the polymerization time is controlled to be 0.5-3h; then a silicon source is added to carry out a hydrolysis-condensation reaction. After the reaction, the mixture is separated, washed, and dried to obtain SiO2@phenolic resin@SiO2 three-layer core-shell structure precursor microspheres. Step S2. The precursor microspheres are carbonized at high temperature under an inert atmosphere, and the phenolic resin is transformed into an amorphous carbon skeleton to obtain SiO2@SiO2 / C@SiO2 composite microspheres. Step S3. The composite microspheres are etched in a dilute hydrofluoric acid solution to selectively remove some of the silicon dioxide and simultaneously form an internal hollow cavity and a shell mesoporous channel to obtain mesoporous hollow SiO2 / C microspheres. Step S4. The mesoporous hollow SiO2 / C microspheres are uniformly mixed with a lithium source and subjected to a high-temperature solid-phase reaction to convert silicon dioxide into lithium silicate, thereby obtaining mesoporous hollow lithium silicate microspheres.
6. The method for preparing mesoporous hollow lithium silicate microspheres according to claim 5, characterized in that, In step S1, during the polymerization reaction of phenolic monomers and aldehyde monomers, a heteroatom doping source is added simultaneously. The heteroatom doping source is one or more of melamine, thiourea, phytic acid, and urea, and the added mass is 5%-50% of the mass of the phenolic monomers.
7. The method for preparing mesoporous hollow lithium silicate microspheres according to claim 5, characterized in that, In step S4, a second metal source is added simultaneously when mixing with the lithium source. The second metal source is one or more of titanium, zinc, cobalt, and tin sources. The amount added is based on a molar ratio of metal element to silicon element of 0.02-0.2:
1. During the high-temperature solid-phase reaction, a nano-second phase is generated in situ to form a lithium silicate-based heterojunction.
8. The method for preparing mesoporous hollow lithium silicate microspheres according to claim 5, characterized in that, The preparation process of the precursor microspheres in step S1 includes the following steps: First, a first portion of silicon source is added and hydrolyzed to form the first SiO2 core. Then, phenolic monomers are added and polymerized to form the first resin layer. Next, a second portion of silicon source is added and hydrolyzed to form the first SiO2 shell. Then, phenolic monomers are added again and polymerized to form the second resin layer. Finally, a third portion of silicon source is added and hydrolyzed to form the second SiO2 shell. After carbonization, etching, and lithiation, double-shell mesoporous hollow lithium silicate microspheres are obtained. The time difference between polymerization and hydrolysis is controlled to be 2.5-3.5 h to form a SiO2@resin core@SiO2 shell structure. The internal SiO2 / C composite core is retained by carbonization and etching, and then lithium silicate microspheres are obtained by lithiation.
9. The method for preparing mesoporous hollow lithium silicate microspheres according to claim 5, characterized in that, The phenolic monomers in step S1 are one or more of resorcinol and phenol; the aldehyde monomers are one or more of formaldehyde and paraformaldehyde; and the silicon source is at least one of propoxysilane and tetraethyl orthosilicate. The hydrolysis-condensation reaction time in step S1 is 12-36 hours, and the reaction temperature is room temperature; In step S2, the carbonization temperature is 500-800℃, the holding time is 1-4h, and the heating rate is 1-10℃ / min.
10. The method for preparing mesoporous hollow lithium silicate microspheres according to claim 5, characterized in that, In step S3, the mass concentration of the dilute hydrofluoric acid solution is 2%-10%, and the etching time is 0.5-2 hours. The lithium source mentioned in step S4 is one or more of lithium hydroxide, lithium nitrate, lithium carbonate, and lithium acetate; the silicon-lithium molar ratio is 1:(1-4), the lithiation reaction temperature is 500-800℃, and the holding time is 2-6h; The microspheres are used in lithium-ion battery anode materials, carbon dioxide adsorbents, catalyst supports, and controlled release supports for active substances.